Comparison of Lymphocyte Neutrophil Ratio in Head Injury Patients with Blood and without Intracranial Bleeding in Dr. M. Djamil Hospital - Syaiful Saanin; Hesty Lidya Ningsih; Abdul Hafiz, Muhammad Zaki (Biomedical Journal of Indonesia, 2021)
A B S T R A C TBackground: Head injuries occur every 15 seconds worldwide, with patientsdying every 12 minutes. The value of the Neutrophil Lymphocyte Ratio (NLR) is afactor that influences the assessment and prognostic value of patients withintracranial hemorrhage and without intracranial hemorrhage in head injury.The aim of this study was to determine the relationship between increased NLRbased on the severity of head injury patients with or without intracranialhemorrhage. Methods: This study is a retrospective cross sectional study of headinjury patients with hemorrhage and without intracranial hemorrhage who weretreated at Dr. M. Djamil Hospital Padang in 2020 from May to December 2020.Data was collected in the Medical Records Department of Dr. M. Djamil HospitalPadang who met the inclusion and exclusion criteria. Results : A total of 92patients were included in the inclusion criteria for this study. The results showedthat the mean NLR value in head injury patients was 11.72 with a variation of7.31. The mean NLR level based on the severity of mild head injury was 10.15with a variation of 6.38. The mean NLR level of moderate head injury severity was12.70 with a variation of 7.09. The mean NLR level of severe head injury, was14.69 with a variation of 9.30. The results showed that there was no difference inthe mean of NLR levels in mild head injury patients with hemorrhage and withoutintracranial hemorrhage. The results showed that there was a significantrelationship between NLR levels in moderate head injury patients withhemorrhage (14.20) and without intracranial hemorrhage (7.20) (p value = 0.029),whereas in severe head injury it could not be assessed because there was nosample without hemorrhage. Conclusion: There is an association betweenincreased NLR and intracranial bleeding in moderate head injury patients